Synergy of the Three Pillars' Roles in Building Sustainable Community Legal Awareness - Riyanto, Riyanto (International Journal of Law Society Services, 2024)
Abstraksi Community legal awareness is the main foundation in creating an orderly and harmonious social life. The role of the three pillars, namely Bhabinsa, Bhabinkamtibmas, and village officials, is a strategic element in building sustainable legal awareness. This study aims to analyse the synergy of the roles of the three pillars in increasing community understanding, compliance and awareness of the law. Using a descriptive qualitative approach, data was obtained through in-depth interviews, field observations, and review of relevant documents. The results showed that collaboration between Bhabinsa, Bhabinkamtibmas, and village officials was effective in improving understanding of the law through education, mediation, and deliberation-based conflict resolution. Support from programmes such as law socialisation, joint patrols, and community empowerment also strengthen this synergy. However, the research also found several obstacles, such as limited resources, the level of community education, and resistance to changing habits. In conclusion, the three-pillar synergy contributes significantly to building community legal awareness in a sustainable manner. To achieve optimal sustainability, it is necessary to increase the capacity of human resources, adequate budget allocation, and support for wider community participation.Keywords: Three Pillars, Legal Awareness, Community